2020
DOI: 10.3390/ijms21176169
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetime and Intensity of Thioflavin T as Reporters of Different Fibrillation Stages: Insights Obtained from Fluorescence Up-Conversion and Particle Size Distribution Measurements

Abstract: Thioflavin T (ThT) assay is extensively used for studying fibrillation kinetics in vitro. However, the differences in the time course of ThT fluorescence intensity and lifetime and other physical parameters of the system, such as particle size distribution, raise questions about the correct interpretation of the aggregation kinetics. In this work, we focused on the investigation of the mechanisms, which underlay the difference in sensitivity of ThT fluorescence intensity and lifetime to the formation of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The autofluorescence decay curve obtained for the phenylalanine fibrils revealed the presence of 0.35-and 2.53-ns decay times after fitting to a biexponential model (Figure 4D). However, the temporal resolution, or the width of the instrument response function (IRF) of the fluorescence lifetime imaging setup, which employs the standard time-correlated single photon counting technique, is $50 ps and does not allow for detecting any ultrafast decay components, which will be completely masked by the 50-ps IRF (Rovnyagina et al, 2019(Rovnyagina et al, , 2020. Hence, we have utilized the fluorescence up-conversion technique, which provides for sub-picosecond resolution of fluorescence decay (for more information, see STAR Methods).…”
Section: Ll Open Access Iscience Articlementioning
confidence: 99%
“…The autofluorescence decay curve obtained for the phenylalanine fibrils revealed the presence of 0.35-and 2.53-ns decay times after fitting to a biexponential model (Figure 4D). However, the temporal resolution, or the width of the instrument response function (IRF) of the fluorescence lifetime imaging setup, which employs the standard time-correlated single photon counting technique, is $50 ps and does not allow for detecting any ultrafast decay components, which will be completely masked by the 50-ps IRF (Rovnyagina et al, 2019(Rovnyagina et al, , 2020. Hence, we have utilized the fluorescence up-conversion technique, which provides for sub-picosecond resolution of fluorescence decay (for more information, see STAR Methods).…”
Section: Ll Open Access Iscience Articlementioning
confidence: 99%
“…50 Shirshin et al indicated that the oxidation processes caused the autofluorescence of protein fibrils. 51 In addition, the intrinsic fluorescence also induced autofluorescence by the aromatic residues in proteins. In this study, the autofluorescence ability was found after assembly; we detected the maximum absorption at 561 nm for β-LG self-assemblies, while native β-LG showed the maximum absorption at 338 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Muschol et al revealed that carbonyl caused the autofluorescence of proteins and amino acids . Shirshin et al indicated that the oxidation processes caused the autofluorescence of protein fibrils . In addition, the intrinsic fluorescence also induced autofluorescence by the aromatic residues in proteins.…”
Section: Resultsmentioning
confidence: 99%
“…However, the temporal resolution, or the width of the instrument response function (IRF) of the fluorescence lifetime imaging setup, which employs the standard time-correlated single photon counting technique, is ~50 ps and does not allow for detecting any ultrafast decay components, which will be completely masked by the 50 ps IRF. 36,37 Hence, we have utilized the fluorescence up-conversion technique, which provides for sub-picosecond resolution of fluorescence decay (for more information, see 'Experimental Section').…”
Section: Resultsmentioning
confidence: 99%